Socio-Economic Characteristics and Present Scenario of Sheep Farmers at Sherpur District In Bangladesh (SAARC Journal of Agriculture, 2021)
This study was aimed to investigate the socio-economic characteristics and present scenario of farmers engaged in sheep production at Sherpur district in Bangladesh. Data were primarily collected with a pre-tested interview schedule from the local sheep farmers. Results showed that average family size, male and female ratio and age was 5.58, 3:10, and 45.23 year, respectively. Family size, land size and yearly livestock income was found significant (P